Rhabdomyolysis Associated with Parainfluenza Virus - Miltiadis Douvoyiannis; Johanna M. Kielbasa; Gopal M. Chandrasekharan; Cynthia L. Holmes; Michael R. Gomez (Case Reports in Infectious Diseases)
Influenza virus is the most frequently reported viral cause of rhabdomyolysis. A 7-year-old child is presented with rhabdomyolysis associated with parainfluenza type 2 virus. Nine cases of rhabdomyolysis associated with parainfluenza virus have been reported. Complications may include electrolyte disturbances, acute renal failure, and compartment syndrome.